Distinct coordination geometries in bis[N,N-bis(2-methoxyethyl)dithiocarbamato-κ2S,S′]diphenyltin(IV) and bis[N-(2-methoxyethyl)-N-methyldithiocarbamato-κ2S,S′]diphenyltin(IV): crystal structures and Hirshfeld surface analysis - Rapidah Mohamad; Normah Awang; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The crystal and molecular structures of two diphenyltin bis(dithiocarbamate)s, [Sn(C6H5)2(C5H10NOS2)2], (I), and [Sn(C6H5)2(C7H14NO2S2)2], (II), are described. In (I), in which the metal atom lies on a twofold rotation axis, the dithiocarbamate ligand coordinates with approximately equal Sn-S bond lengths and the ipso-C atoms of the Sn-bound phenyl groups occupy cis-positions in the resulting octahedral C2S4 donor set. A quite distinct coordination geometry is noted in (II), arising as a result of quite disparate Sn-S bond lengths. Here, the four S-donors define a trapezoidal plane with the ipso-C atoms lying over the weaker of the Sn-S bonds so that the C2S4 donor set defines a skewed trapezoidal bipyramid. The packing of (I) features supramolecular layers in the ab plane sustained by methylene-C-H...[pi](Sn-aryl) interactions; these stack along the c-axis direction with no specific interactions between them. In (II), supramolecular chains along the b-axis direction are formed by methylene-C-O(ether) interactions; these pack with no directional interactions between them. A Hirshfeld surface analysis was conducted on both (I) and (II) and revealed the dominance of H...H interactions contributing to the respective surfaces, i.e. >60% in each case, and other features consistent with the description of the molecular packing above.